Balancing future food security and greenhouse-gas emissions from animal-sourced protein foods in Southeast Asia - Hegarty, R. S.; Tee, T. P.; Liang, J. B.; Abu Hassim, H.; Zainudin, M. H. M.; Azizi, A. A.; Widiawati, Y.; Pok, S.; Candyrine, S. C. L.; Rusli, N. D. (CSIRO Publishing, 2024)
Abstract Southeast Asia’s human population is expected to rise by 100 M between 2023 and 2050, with an associated rise in animal product output in the region’s low- to middle-income countries. Countries with the largest population are forecast to continue their increasing poultry consumption, with regional pig meat consumption also to rise, but much less than in China to the north, and much less in Muslim dominant countries. The forecast growth in the regional ruminant population is more modest and the farm gate greenhouse gas (GHG) cost per unit of human food protein generated is much higher for ruminant meat (203-584 kg CO2e/ kg protein) than for pig meat (18 kg/kg) or poultry (4 kg/kg). Changing human diets away from ruminant or any animal-sourced protein, is being explored to increase the human food supply at a lower GHG cost. However, with small-holder livestock production systems dominant across many regional countries, the social, land-use and broader economic roles of ruminants need consideration. Strategies to expand ruminant production but with a reduced greenhouse gas unit cost (emission intensity) are being pursued. Increasing individual animal product output, largely through simple animal health and nutritional management decisions, can allow future food targets to be met at a lower GHG emission than if this additional food was produced by business-as-usual livestock production systems. Since the Paris Agreement recognises the priority of food provision over emission abatement, it seems reasonable that much of Southeast Asia should pursue emission intensity targets more than absolute emissions targets and reflect this in their Nationally Determined Contributions (NDCs). Emission intensity intentions are already apparent not just in NDCs but in emerging carbon markets.